Barriers in Marketing Public Relations and Narrative Paradigm Theory - Tresna Wiwitan; Neni Yulianita; Sophia Novita (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Universities are becoming increasingly competitive in attracting prospective students. Various Marketing and Public Relations activities, whether direct or mediated, are carried out to attract the interest of prospective students. This study aims to identify; barriers to Marketing PR activities in universities and solutions to overcome these obstacles. This research uses a qualitative case study with a multi-case design. The research object consists of the Public Relations Departments of the Islamic University of Bandung and the Islamic University of Sultan Agung Semarang. The reason for choosing these two universities is that they are members of the Coordinating Board for Private Islamic Universities and are institutionally accredited with Superior. The data collection techniques used in this study were in-depth interviews, observation, discussion, and literature review. The informants in the study consisted of seven (7) people: the head of public relations, public relations staff, and the vice-chancellor in charge of the public relations department. The results of this study are expected to help university public relations anticipate and overcome obstacles in Marketing PR activities by using the theory of the narrative paradigm. Public relations must have the ability to tell stories using narratives that are based on data from the field and touch on aspects of public emotion